Effect of graphene nanoparticle addition in YBa₂Cu₃Oy using thermal treatment method and fabrication of YBa₂Cu₃Oy with various liquid phase ratios via infiltration growth - Kamarudin, Aliah Nursyahirah (2021)
In this study, the superconducting properties of YBa2Cu3O7-δ (Y123) were studied using the thermal treatment method and the infiltration growth (IG) method. The synthesis of Y123 with graphene nanoparticles addition was prepared by the thermal treatment method using polyvinyl pyrrolidone (PVP) as a capping agent. Meanwhile, utilizing the liquid phase source of Y123 superconductors was studied by varying the Y123:ErBa2Cu3Oy (Er123) ratios fabricated by the IG method. The microstructure and superconducting properties of Y123 were investigated by thermogravimetric analysis (TGA), X-ray diffraction (XRD), field-emission scanning electron microscope (FESEM), energy dispersive X-ray diffraction (EDX), alternating current susceptibility (ACS), and SQUID magnetometer. It was found that all samples were indexed with a Pmmm orthorhombic crystal structure with Y123 as the major phase followed by a secondary phase of Y211. The increasing weight percentage up to 97.1 % of Y123 major phase in sample x = 0.3 wt. % added with graphene nanoparticles showed that this impurity was capable of enhancing the Y123 phase purity. The addition of graphene nanoparticles promoted into closely packed and denser, thus giving rise to the better grain growth of Y123 with less porosity. From the AC susceptibility, the highest Tc-onset obtained in sample x = 1.0 wt. %, followed by x = 0.5 wt. % with 92.64 K and 92.59 K, respectively. The improvement of the Jcm, at sample x = 1.0 wt. %, 25.94 A/cm2 was observed. It showed that graphene nanoparticles acted as pinning centers, improving the Jcm. In the IG method, the formation of smaller Y211 particles in IG samples with uniform distributions was also found to act as an effective pinning center. Hence, the critical current density, Jc of the sample Y1Er0 at 77 K with H//c-axis had the highest Jc 54.15 kA/cm2 and 11.45 kA/cm2 at self-field and 2 T, respectively. In conclusion, the existence of graphene nanoparticles and uniform distribution of the Y211 secondary phase plays an important role as an optimum flux pinning center to obtain good bulk of Y123 superconductors.